Pertumbuhan, Kelangsungan Hidup dan Efisiensi Pakan Ikan Lele Sangkuriang (Clarias gariepinus) Yang Diberi Campuran Sinbiotik ke Dalam Pakan - Pardiansyah, Dedi; Pratama, Andi Komandala; Utami, Risnita Tri; Zulkhasyni, Zulkhasyni (Jurnal Akuakultur Sungai dan Danau, 2026)
Commercial feed usually accounts for 60-70% of the total production costs in aquaculture. Therefore, feed additives are needed to support fish growth and feed efficiency to reduce production costs. This study aims to determine the effect of adding a synbiotic mixture to the feed of Sangkuriang catfish (Clarias gariepinus). This research utilized a Completely Randomized Design (CRD) consisting of 4 treatments with 4 replications, resulting in 16 experimental units. The best average absolute weight and absolute length growth of Sangkuriang catfish fingerlings were found in treatment P4 with a 25% synbiotic mixture. Observations on fish survival rates showed the best results with the inclusion of the synbiotic mixture in the feed.The highest feed efficiency was obtained in treatments P4 and P3, with an average of 0.80%, meaning that 80% of the feed was effectively utilized for daily needs. This was followed by treatment P2 at 0.78%, while the lowest efficiency was found in treatment P1 at 0.77%. The results indicated that all treatments were significantly different. Analysis showed that the lowest Feed Conversion Ratio (FCR) was obtained in P4 (25% synbiotic) and P3 (20% synbiotic), both showing an average value of 1.25%. P2 (15% synbiotic) followed with 1.29%, and P1 (10% synbiotic) with 1.30%, which remains within the standard threshold. Water quality parameters monitored during the study included temperature, pH, and dissolved oxygen